(untitled) (Journal of Human Sciences, 2026)
This paper is the result of fieldwork I conducted from June 8, 2004, to June 13, 2004, when I was a graduate student. The study was based on the city of Ghat and its environs. The subject of this study revolves around the belief or custom of visiting shrines among the Tuareg (in Ghat), which was also practiced by several other peoples. This belief represents a degree of religious thought and is closely linked to it. The custom of visiting shrines is generally linked to the religious thought of man, as he considered them to represent a mediator between him and his God, not the shrine itself, but rather the person in it or the one who occupies this position (mediation), who acquired it as a result of the components determined by the mentality of the people, which is often religious in nature. There are many questions surrounding the origin of this custom. It may have been introduced by Sufis to Tuareg areas during the spread of Islam and the Islamic conquests in those regions. It may have its roots in the customs of African peoples, or it may be a product of the Tuareg people’s adaptation of the old (customs and traditions like those of African peoples) and the new (ideas and beliefs brought by Islam and Muslims). This custom may represent an integrated framework in which everything is linked to an aspect of Tuareg life. It is an authentic framework, unrelated to external influences, except for superficial effectiveness.